In vitro evaluation of stearylamine cationic nanoemulsions for improved ocular drug delivery - Dukovski Bisera Jurišić; Bračko Ana; Šare Marija; Pepić Ivan; Lovrić Jasmina (Acta Pharmaceutica)
Oil-in-water nanoemulsions (NEs) represent one of the formulation approaches to improve eye-related bio-availability of lipophilic drugs. The potential of cationic NEs is pronounced due to the electrostatic interaction of positively charged droplets with negatively charged mucins present in the tear film, providing prolonged formulation residence at the ocular surface. The aim of this study was to develop a cationic ophthalmic NE with cationic lipid stearylamine (SA) as a carrier of a positive charge. The addition of a nonionic surfactant provided the dual electro-steric stabilization of NEs and enabled tuning of SA concentration to achieve an optimal balance between its interaction with mucins and biocompatibility. Physicochemical characterization, stability profile, in vitro mucoadhesion study and biocompatibility study employing 3D HCE-T cell-based model of corneal epithelium pointed out the NE with 0.05 % (m/m) SA as the leading formulation. Minimizing SA content while retaining droplet/mucin interactions is of great importance for efficacy and safety of future ophthalmic drug products.